High‐definition endoscopy with iScan and Lugol's solution for the detection of inflammation in patients with nonerosive reflux disease: histologic evaluation in comparison with a control group. Issue 2 (17th December 2014) - Rey, J. W.; Deris, N.; Marquardt, J. U.; Thomaidis, T.; Moehler, M.; Kittner, J. M.; Nguyen‐Tat, M.; Dümcke, S.; Tresch, A.; Biesterfeld, S.; Goetz, M.; Mudter, J.; et al.
Summary: Nonerosive reflux disease (NERD) is commonly diagnosed in patients with symptoms of reflux. The aim of the present study was to determine whether high‐definition endoscopy (HD) plus equipped with the i Scan function or chromoendoscopy with Lugol's solution might permit the differentiation of NERD patients from those without reflux symptoms, proven by targeted biopsies of endoscopic lesions. A total of 100 patients without regular intake of proton pump inhibitors and with a normal conventional upper endoscopy were prospectively divided into NERD patients and controls. A second upper endoscopy was performed using HD+ with additional i Scan function and then Lugol's solution was applied. Biopsy specimens were taken from the gastroesophageal junction in all patients. A total of 65 patients with reflux symptoms and 27 controls were included. HD + endoscopy with i Scan revealed subtle mucosal breaks in 52 patients; the subsequent biopsies confirmed esophagitis in all cases. After Lugol's solution, 58 patients showed mucosal breaks. Sensitivity for the i Scan procedure was 82.5%, whereas that for Lugol's solution was 92.06%. Excellent positive predictive values of 100% and 98.3%, respectively, were noted. The present study suggests that the majority of patients with NERD and typical symptoms of reflux disease can be identified by i Scan or Lugol's chromoendoscopy as minimal erosive reﬂux disease (ERD) patients.